THE ROLE OF MANAGERIAL OWNERSHIP AS MODERATION ON FACTORS AFFECTING DEBT POLICY IN COMPANIES WITH LARGE MARKET CAPITALIZATION IN INDONESIA - Windy, Windy; Lukman, Hendro (Graduate Program of Universitas Tarumanagara, 2023)
the goal of this study was to gather empirical evidence of the effect of Profitability, Dividend Policy, and Collateral Assets on Debt Policy with Managerial Ownership as a moderating variable. This research relies on secondary data from the Indonesia Stock Exchange (IDX). The population used in this study are companies with large capitalization values that are included in the LQ45 index in the 2016-2020 period. Sampling in this study used purposive sampling method, and the data that met the criteria were 70 data which were processed using Statistical Package for the Social Sciences (SPSS) vers 25.0. Partially, Profitability and Collateral Assets have a significant impact on Debt Policy, while Dividend Policy has no significant effect on Debt Policy. Managerial Ownership unable to moderate the effect of Profitability, Dividend Policy and Collateral Assets on Debt Policy. The implication of this research is that companies with large capitalization of managerial ownership should play a greater role in determining debt policy by maintaining the level of profitability and collateral assets.